Eat. lift. thrive. - Lee, Sohee 1989- (Champaign, IL Human Kinetics, 2017)
More than an exercise guide, the book Eat. Lift. Thrive. acknowledges and addresses the relationship women have with fitness and food. Popular trainer and author Sohee Lee shares her experience and strategies for overhauling mindset, eating habits, and training routines. Detailed instructions, color photos, and advice accompany Lee's nutrition tips, exercises, and 12-week program.
Part I-Reset Your Thinking; Chapter 1-Forget What You Know; Chapter 2-Falling Forward; Chapter 3-You're Not Alone; Part II-Eat; Chapter 4-Nutrition Basics; Chapter 5-Living-Lean Guidelines; Chapter 6-Embrace Moderation; Chapter 7-Level Up With Resistance Training; Part III-Lift; Chapter 8-Primary Strength Movements; Chapter 9-Cardio and Glute Circuits; Part IV-Thrive; Chapter 10-Create Your Program; Chapter 11-Sample Programs; Chapter 12-Monitor Your Progress.
Includes bibliographical references (pages 227-232) and index.
Keywords: Women -- Health and hygiene; Physical fitness for women